O atual mercado de trabalho para o bibliotecário no Estado do Ceará - Tabosa, Hamilton Rodrigues (2011)
Aims to meet the general fields of effective participation of librarians in Ceará. Specific objectives: a) identify the spaces occupied by librarians working in Ceará state, b) check what the requirements and needs of the labor market for librarian c) identify the market sectors that absorb most of the labor- librarian work and d) to characterize the job market for librarians in the state of Ceará. In theoretical talk about the profession in Library (the concept of profession, the profession of librarian and librarian) and the labor market. Regarding methodology, we use the literature in order to select material for later use in the theory on the subject. To collect data we used the questionnaire in a semi-open, which was applied to librarians Ceará recorded in the CRB-3, through the tool Google Docs. We conclude, through most of the answers that the job market for librarians in Ceará is predominantly traditional, composed of university libraries of private institutions, paying between U.S. $ 1,001.00 to $ 2,000.00 for professionals who work 40 hours per week. We also notice that the labor market demands of professional administrative and technical functions; mostly requires only supports graduate and professional continuing education, among other features.